Talazoparib Does Not Interact with ABCB1 Transporter or Cytochrome P450s, but Modulates Multidrug Resistance Mediated by ABCC1 and ABCG2: An in Vitro and Ex Vivo Study - Sabet, Ziba; Vagiannis, Dimitrios; Budagaga, Youssif; Zhang, Yu; Novotná, Eva; Hanke, Ivo; Rozkoš, Tomáš; Hofman, Jakub (International journal of molecular sciences, 2022)
Talazoparib (Talzenna) is a novel poly (adenosine diphosphate-ribose) polymerase (PARP) inhibitor that is clinically used for the therapy of breast cancer. Furthermore, the drug has shown antitumor activity against different cancer types, including non-small cell lung cancer (NSCLC). In this work, we investigated the possible inhibitory interactions of talazoparib toward selected ATP-binding cassette (ABC) drug efflux transporters and cytochrome P450 biotransformation enzymes (CYPs) and evaluated its position in multidrug resistance (MDR). In accumulation studies, talazoparib interacted with the ABCC1 and ABCG2 transporters, but there were no significant effects on ABCB1. Furthermore, incubation assays revealed a negligible capacity of the tested drug to inhibit clinically relevant CYPs. In in vitro drug combination experiments, talazoparib synergistically reversed daunorubicin and mitoxantrone resistance in cells with ABCC1 and ABCG2 expression, respectively. Importantly, the position of an effective MDR modulator was further confirmed in drug combinations performed in ex vivo NSCLC patients-derived explants, whereas the possible victim role was refuted in comparative proliferation experiments. In addition, talazoparib had no significant effects on the mRNA-level expressions of MDR-related ABC transporters in the MCF-7 cellular model. In summary, our study presents a comprehensive overview on the pharmacokinetic drug-drug interactions (DDI) profile of talazoparib. Moreover, we introduced talazoparib as an efficient MDR antagonist.
Keywords: Cytochrome P-450 Enzyme System; Carcinoma, Non-Small-Cell Lung; cytochrome P450; ATP-Binding Cassette Transporters; pharmacokinetic drug–drug interaction; ATP Binding Cassette Transporter, Subfamily B; Humans; systém (enzymů) cytochromů P-450; small cell lung cancer; Drug Resistance, Multiple; P-glykoproteiny; ABC transporter; ABC transportéry; ABC transportér z rodiny G, člen 2; talazoparib; Lung Neoplasms; nemalobuněčný karcinom plic; mnohočetná léková rezistence; multidrug resistance; Neoplasm Proteins; ATP Binding Cassette Transporter, Subfamily G, Member 2; lidé; nádory plic; nádorové proteiny